Comparison of the discounted costs of controlled asynchronous electric drives with matrix and with DC link frequency converters - Petrushyn, Viktor; Plotkin, Juriy; Horoshko, Vasily; Yenoktaiev, Rostyslav; Yakimets, Andrii (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
A quality criterion based on discounted costs is proposed, which demonstrates a significant advantage of the variable frequency asynchronous motor drive with a matrix converter over the drive with a voltage source inverter, which contains a DC link. A MATLAB software simulation was conducted to ascertain the control characteristics. In light of the control range afforded by both drives, a criterion for discounted costs is proposed that is calculated as a mid-range within a specific rotational speed control range, or is determined based on a given tachogram. The aforementioned costs include the expense of the drive, the cost of losses, maintenance costs, amortization charges, and the cost of reactive power compensation due to phase shifts of the main harmonic current and voltage. In this study, we put forth a novel proposal for the incorporation of the cost of distortion power compensation resulting from the presence of harmonic components of the input current.  The latter costs characterize the electromagnetic compatibility of the drive with the network. For the first time, a quality criterion for a regulated electric drive is proposed, which has a cost component that takes into account the electromagnetic compatibility of the drive with the network. A significant reduction in this component in a drive with a matrix converter compared to a drive with a DC link predetermines a reduction in discounted costs. For a given payback period and annual inflation rate, it was determined that the mid-range discounted costs were reduced by more than 11 times and the tachogram based discounted costs were reduced by more than 10 times for a drive with a matrix converter in comparison to a drive with a DC link.